1994
DOI: 10.1016/0020-7292(94)90580-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and silicone breast implants

Abstract: Since 1962, breast implants made of a silicone elastomer envelope filled with either silicone or saline have been used by an estimated l-2 million women in the United States alone. Given that women in the United States have a lifetime risk of breast cancer of approximately 1 l%, and the concerns which have been expressed about the risks associated with the use of silicone breast implants, we reviewed the medical literature to thoroughly evaluate the risks of breast cancer to users of these implants.Our review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…First, the liquid silicone used for injection has been shown to occasionally contain additives which may have sometimes been of a non-medical grade. Second, the physiological response to liquid silicone may be different from that of vulcanized silicones, such as silicone gels [ 1 ]. Furthermore, Felix et al reported the tumorigenicity of silicone gels in the mouse plasmacytoma system [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the liquid silicone used for injection has been shown to occasionally contain additives which may have sometimes been of a non-medical grade. Second, the physiological response to liquid silicone may be different from that of vulcanized silicones, such as silicone gels [ 1 ]. Furthermore, Felix et al reported the tumorigenicity of silicone gels in the mouse plasmacytoma system [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although breast cancer after augmentation mammoplasty has been reported and the causal relationships between foreign bodies in the breast and carcinogenesis have been reviewed, so far no definitive consensus opinion has been obtained [ 1 - 11 ]. This report describes a unique case of multiple invasive micropapillary carcinomas (IMPCs) of the breast arising 42 years after augmentation mammoplasty by the injection of liquid silicone.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, no evidence was found to associate the use of silicone breast implants with either an increased risk of breast cancer or an increased risk of a more advanced stage of cancer at the time of cancer diagnosis, compared to women not using breast implants [6].…”
Section: Risks Associated With the Use Of Breast Implantsmentioning
confidence: 99%
“…Another retrospective case‐controlled study found that the average stage of cancer detected in women with implants was less advanced than the stage of cancer in patients without implants 39 . However, interpretation of these results is clouded by the small sample sizes, known referral bias, and design flaws such as the failure to obtain preaugmentation baseline mammograms 1,23,49 …”
Section: Implants and Breast Cancer Diagnosis/prognosismentioning
confidence: 99%
“…Nearly 2 million women in the United States have undergone augmentation mammoplasty, one of the most frequent plastic surgery procedures 1 . In 2000, approximately 300,000 women in the United States had this surgery performed 2 .…”
mentioning
confidence: 99%